MODEL SISTEM ANTREAN PADA KEDATANGAN DAN KEPERGIAN PELANGGAN DI CIRCLE K SURAPATI DENPASAR - YONI, DESAK MADE NIRMALA; MEILIANA, NI LUH; OCTAVANNY, MADE AYU DWI (E-Jurnal Matematika, 2026)
This study aims to analyze the queueing model based on the customer arrival and departure dynamics at Circle K Surapati, Denpasar. The study uses primary data obtained by recording customer arrival and departure times during a single observation period from 15:00 to 17:30 WITA. The results show that the arrival rate increases from 1.6 customers per 10 minutes at state 0 to 18 customers per 10 minutes at state 3, while the departure rate decreases from 4.4 customers per 10 minutes at state 1 to 1.5 customers per 10 minutes at state 4. The highest steady-state probability occurs at state 4 (0.8279), indicating that this condition most frequently appears in the long run. Furthermore, the Chi-Square goodness-of-fit test reveals that both interarrival and service time do not follow exponential distributions. Consequently, the system is best represented by a general distribution queueing model. The system is identified as a : queueing model, utilizing two active service facilities under a first come-first served discipline